Thermodynamic Characterization of Surface and Solubility of 5-((S)-3,7-Dimethyloctyloxy)-2-[[[4-(octyloxy)phenyl]imino]methyl]phenol Liquid Crystal with Some Solvents - Yanic, Serap Mutlu; Cakar, Fatih; Ocak, Hale; Karaman, Ferdane; Cankurtaran, Ozlem; Eran, Belkiz Bilgin (AMER CHEMICAL SOC, 2019)
The inverse gas chromatography method was used to obtain dispersive surface energy, surface acidity or basicity constants, mole fraction activity coefficients of the solvents at infinite dilution for a new salicylaldimine based chiral calamitic liquid crystal 5-((S)-3,7dimethyloctyloxy)-2-[[[4-(octyloxy)phenyl]imino]methyl]phenol (DOPIMP). The dispersive surface energy of DOPIMP was estimated as 41.1 mJ/m(2) at 30 degrees C and decreased with temperature. The specific free energy, enthalpy, and entropy of adsorption of the selected polar solvents on the liquid crystal were determined. The values of adsorption enthalpy were correlated with both donor and acceptor numbers of the solvents to quantify acidic KA and basic KD parameters of the liquid crystal surface. The results indicated that the surface of DOPIMP is basic. The retention diagrams of n-hexane, n-heptane, n-octane, n-nonane, n-decane, undecane, ethyl acetate, n-butyl acetate, iso-butyl acetate, toluene, ethylbenzene, n-propylbenzene, and chlorobenzene on the DOPIMP were plotted as straight lines using the net retention volumes at temperatures between 368.2 and 398.2 K. The values of activity coefficients indicated that DOPIMP was better soluble in long chain alkanes. Negatively signed partial molar Gibbs energies of mixing were obtained at infinite dilution of studied solvents.
Keywords: INVERSE GAS-CHROMATOGRAPHY; MESOMORPHISM; COEFFICIENTS; Thermodynamics; Chemistry; Engineering